Comparison of different methods in estimating potential evapotranspiration - Ayu Shakira, Shafie (2016)
Evapotranspiration (ET) is a term used to describe the sum of evaporation and transpiration form land surface to atmosphere. Considering the importance of ET, two methods was developed to estimate potential evapotranspiration (PET). The two ET groups there are temperature-based method and radiation-based method. About two types of PET methods were selected for each groups there are Priestly-Taylor Method and Turc Method to represent radiation-based method, meanwhile Hargreaves-Samani Method and Blaney-Criddle Method represented temperature-based method. The A2 scenario is used to represent the level of state development due to the climate projection results. The daily temperature data was provided by MMD under Ministry Science. The data provided was used in the method to estimate the future trend of PET in long term. Downscaling is a technique that have been used to predict the local meteorological condition. The SDSM is a tool that used to produce high resolution climate change scenario. The objective of the study was to quantify the performance between radiation-based method and temperature-based method and to analyse the future trend of ET at Kuantan, Pahang state. In this study, it was found that the radiation-based method gave better performance compared to temperature-based method in quantifying in calculating ET. In radiation-based method, Priestly-Taylor Methods is the most suitable method to use to find ET based on the lowest value of absolute error and higher Pearson error. Projection temperature results for minimum, mean and minimum will increase in every 30 years for interval year 2010-2039, 2040-2069 and 2099. From the projecting temperature, Turc Method under radiation-based method are suitable for projecting changing pattern of ET under climate change scenario. On the other hand, accuracy and reliability of simple PET models vary widely according to climate condition.